Effective Microorganisms: Myth or reality? - Cóndor_Golec, Aníbal F. (2007)
Th e increase in population has lead to intensifi cation of agricultural systems. Due to the use of pesticides the productivity of agricultural systems has increased but environmental deterioration and unsustainable systems are the consequences of these ways of management. Th e environmentally friendly Eff ective Microorganisms (EM) technology claims an enormous amount of benefi ts (claimed by the companies). Th e use of EM as an addictive to manure or as a spray directly in the fi elds may increase the microfauna diversity of the soil and many benefi ts are derived from that increase. It seems that suffi cient information is available about this new technology. Th e aim of this project is to make an analysis of the literature about EM and answer the following questions: 1) how much is known about EM?, 2) how much research is done on EM?, 3) what are the principals of EM?, what are the socio-economic implications of EM?. We want to answer these questions in order to publish the facts about EM and its socio-economic implications.